1994
DOI: 10.1038/bjc.1994.265
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological and clinical evaluation of two doses of formestane in advanced breast cancer

Abstract: Smmary Formestane is a selective inhibitor of oestrogen synthesis by aromatase enzymes and induces disease regression in breast cancer patients. This phase II randomised study was carried out to determine whether there were any differences in the effects of two different doses of formestane on oestradiol (E2) serum levels and to evaluate the corresponding clinical activity in post-menopausal patients with positive or unknown oestrogen receptor status pretreated or not for advanced disease. Furthermore, possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…2). [19,22] Plasma estrone and estrone sulfate levels fell in parallel with estradiol levels during treatment with intramuscular formestane[2I,27] (by 64, 68.S and 61 %, respectively, in one study [27]). …”
Section: Studies In Women With Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…2). [19,22] Plasma estrone and estrone sulfate levels fell in parallel with estradiol levels during treatment with intramuscular formestane[2I,27] (by 64, 68.S and 61 %, respectively, in one study [27]). …”
Section: Studies In Women With Breast Cancermentioning
confidence: 99%
“…Soft tissue metastases generally responded best to formestane, whereas visceral metastases, particularly those in the liver, were the least respon-siveJ19,39) In a large study, (19) 16 of 48 (33%) and 32 of 56 (57%) soft tissue metastases (skin, lymph nodes and breast) responded to treatment with formestane 250 and 500mg, respectively. Corresponding mean response rates in visceral metastases (liver, lung and pleural effusion) were 30 and 31%, respectively, and in bone, rates were 18 and 37% ( fig.…”
Section: 1 Efficacy As Second-or Thlrd-une Endocrine Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Formestane (4-hydroxyandrostenedione) is a se lective aromatase inhibitor that is capable of reducing plasma estrogen levels by blocking the peripheral conver sion of androgens to estrogens without interfering with adrenal steroidogenesis [3]. The good clinical efficacy of formestane has been demonstrated in a large number of studies [4,5] and, in a previous experiment with the drug, we found a certain activity in postmenopausal advanced breast cancer patients who had already received TMX treatment [6], Given these data, and the fact that only TMX relapse patients are generally considered for sec ond-line endocrine therapy, we decided to test the activity of formestane in de novo resistant patients.…”
Section: Introductionmentioning
confidence: 99%